PENGARUH KESEMPATAN INVESTASI, LIKUIDITAS, LEVERAGE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Ni Made Putri Ratna Suari; Ni Wayan Alit Erlinawati (UNHI Press, 2020)
The purpose of this study to examine thei effect of thei variable investment opportunity set, Liquidity, leveragei and institusionali ownership on dividenid policy. This study uses manufacturing companies listed on the Indonesia Stock Echange period 2016-2018. The number of research population is 140 manufacturing companies, thei researchers used a purposive samplingi method and selected 31 companies that met the creteria. The analysis technique used in thei study is multiple linier regression analysis technique, classic assumption test including normality test, multicolinearity test, heteroskedastisitas test, autokolerasi test, hypothesis testing t-statistic and f-statistic to test thei feasibility of the research model. The result analysis shows that investment opportunity set negative effect, liquidity positive effect, leveragei and institusionali ownership have no effect on dividenid policy on manufacturing companies in Indonesia stock exchange period 2016-2018